2015
DOI: 10.12669/pjms.315.7881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early interventional treatment opportunity of the elderly and high-risk patients with non-ST segment elevation acute myocardial infarction

Abstract: Objective:To investigate the effect of treatment on prognosis of patients with different timing of early interventional treatment for non-ST segment elevation acute myocardial infarction (NSTEMI).Methods:Forty two cases above 75 years old, diagnosed with high-risk on NSTEMI, were selected in cardiology department of Xinxiang central hospital. They were randomly divided into two groups: 22 in group A and 20 in group B. Group A was performed PCI surgery within 12 hours after the onset while group B from 12 to 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(16 reference statements)
0
10
0
Order By: Relevance
“… c In the trials by Liu et al . 18 and Tekin et al ., 17 median timing of ICA for each group was not provided. Timing targets specified in the study methodology are listed.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“… c In the trials by Liu et al . 18 and Tekin et al ., 17 median timing of ICA for each group was not provided. Timing targets specified in the study methodology are listed.…”
Section: Methodsmentioning
confidence: 92%
“… 17 and Liu et al . 18 studies did not provide median timing to angiography data, rather target thresholds for each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at present, the optimal timing of routine invasive intervention is still controversial because of the conflicting reports of existed randomized controlled trials (RCTs) comparing early vs. delayed invasive approaches (Neumann et al, 2003 ; van't Hof et al, 2003 ; Mehta et al, 2009 ; Montalescot et al, 2009 ; Riezebos et al, 2009 ; Sciahbasi et al, 2010 ; Zhang et al, 2010 ; Thiele et al, 2012 ; Badings et al, 2013 ; Tekin et al, 2013 ; Liu et al, 2015 ; Reuter et al, 2015 ; Milosevic et al, 2016 ; Oosterwerff et al, 2016 ). Meta-analysis in recent years has also shown insufficient evidence either in favor of or against an early invasive strategy in the NSTE-ACS population (Navarese et al, 2011 , 2013 ; Milasinovic et al, 2015 ; Jobs et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main limitations of the published meta-analysis was the small number of included studies. After literature retrieval, we updated four new studies (Liu et al, 2015 ; Reuter et al, 2015 ; Milosevic et al, 2016 ; Oosterwerff et al, 2016 ), hoping to gain a further conclusion with a larger sample size. In addition, by observing the data, we found that several studies used “<2 h” as the timing for immediate invasive therapy (Montalescot et al, 2009 ; Riezebos et al, 2009 ; Thiele et al, 2012 ; Milosevic et al, 2016 ; Oosterwerff et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%